1982
DOI: 10.1152/jappl.1982.53.3.756
|View full text |Cite
|
Sign up to set email alerts
|

Action of the diaphragm on the rib cage inferred from a force-balance analysis

Abstract: Displacements of the rib cage are determined by the intrinsic passive properties of the rib cage, rib cage musculature, pleural and abdominal pressures, and the diaphragm. The diaphragm's mechanical actions on the rib cage are inferred from a force-balance analysis in which the diaphragm is seen to cause expansion of the rib cage by pulling cephalad at its insertions on the lower ribs (insertional component) and by raising intra-abdominal pressure, which pushes outward on the diaphragm's zone of apposition to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1
4

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 0 publications
7
77
1
4
Order By: Relevance
“…The diaphragm has a mechanism of expansion that involves not only the abdomen but also the lower thorax. 28 Therefore we assumed that the marker distances of the lower thorax were greater in the male subjects. In the sitting position, female subjects had significantly decreased upper thoracic movement, and there were significant negative relationships between upper thoracic movement and sex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diaphragm has a mechanism of expansion that involves not only the abdomen but also the lower thorax. 28 Therefore we assumed that the marker distances of the lower thorax were greater in the male subjects. In the sitting position, female subjects had significantly decreased upper thoracic movement, and there were significant negative relationships between upper thoracic movement and sex.…”
Section: Discussionmentioning
confidence: 99%
“…Possible causes are more predominant rib cage breathing and higher lung volumes. Loring and Mead 28 showed that the inspiratory action of the diaphragm on the rib cage was greatest at low lung volumes. Accordingly, during deep breathing, which involves higher lung volumes and relatively greater rib cage movement, expansion of the lower rib cage seems to be more difficult in the sitting position than in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…It is tempting to attribute this, at least in part, to the greater mechanical impairment of diaphragmatic function in these patients, compared to those with "isolated" chronic bronchitis or asthma. Nevertheless, both the lowering of pressure difference between peritoneum and pleura (∆Pdi) due to the flattening of the diaphragm [44], and the "intrinsic-PEEP" (auto-PEEP) phenomenon of emphysematous patients [45] should partially act against persistence of atelectasis during consciousness. The possible explanation(s) of this behaviour, as well as the importance of surgical transection of the transversus abdominis muscle (which many COPD patients contract during expiration) [46], are as yet unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Contraction of the diaphragm increases abdominal pressure and decreases pleural pressure. The increased abdominal pressure exerts an outward inspiratory force on the lower third of the rib cage, which is apposed to the diaphragm (34,35). The upward pull of the costal diaphragm also causes the lower rib cage to expand.…”
Section: Mechanical Actions In Situmentioning
confidence: 99%